Influence of Knowledge Management on Organizational Performance at SD N Dasan Bengkel Lombok - Yang, Yang; Nuruly, Santi (Journal of Educational Analytics, 2024)
The quality of management highly influences the implementation of a particular educational institution, which further determines the success of its goals and outcomes. This research aims to investigate the influences of knowledge management on organizational performance at SDN Dasan Bengkel Lombok. A descriptive qualitative research method was employed, partial observation, interviews, and document analysis were used to collect the data from ten participants, including one principal and nine teachers. This study adopted Miles and Huberman's data analysis techniques commenced with data reduction, data display, and verification to analyze the data. The triangulation technique was employed to examine the validity of the data from the three data collection methods. The results demonstrated that knowledge management influences the performance of SDN Dasan Bengkel Lombok school organization, particularly in the aspects of decision-making, innovation in organization, teachers' abilities as members of the school organization, and students' learning outcomes. All the elements are spelt out in the other part of this study. The researcher recommends principals possess knowledge management skills for their school organization.